SMART ENVIRONMENT ROADMAP CONCEPT FOR THE CITY OF PANGKAL PINANG BASED ON LESSONS LEARNED FROM JAKARTA AND MAKASSAR - Febrina Lusianna Manik; Revan Anthony; Oktavian Luthfi Khairan Somali; Master Edison Siregar (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
This study develops a smart environment roadmap for Pangkalpinang by learning from the experiences of Jakarta and Makassar. Smart environment is positioned as a key pillar of smart city development because it supports sustainable management of air, water, waste, energy, and disaster risk. The research uses a qualitative descriptive approach with comparative case study design. Data are obtained from scientific literature, government documents, and official publications related to smart environment initiatives in the three cities, then analysed using content analysis and cross-case comparison. The findings show that Pangkalpinang is still at an early stage of smart environment development, characterised by limited digital infrastructure, fragmented environmental data, and low levels of digital participation. Jakarta represents a technology-driven model with strong data integration, while Makassar prioritises community participation and context-sensitive innovation. Based on these lessons, the study proposes a phased roadmap consisting of twelve programmes (EN15–1 to EN15–12) that gradually strengthen monitoring infrastructure, data integration, public awareness, smart waste management, smart energy, and coastal environmental monitoring. The roadmap is expected to guide local governments in planning realistic and sustainable smart environment development.